2020
DOI: 10.5713/ajas.19.0055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of including n-3/n-6 fatty acid feed sources in diet on fertility and hatchability of broiler breeders and post-hatch performance and carcass parameters of progeny

Abstract: The present trial was conducted to determine the influence of different dietary fatty acid (omega-3 and omega-6) sources on reproductive performance of female broiler breeders and growth performance and carcass traits of their progeny. Methods: Two hundred and twenty, 25 weeks old Ross-308 male (20) and female (200) broiler breeders were used in the experiment for the period of 6 weeks. All birds were randomly divided into four dietary treatments (containing 2% soybean oil, 2% sunflower oil, 2% flaxseed oil, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In the current study, the organic Cu improved the fertility, hatchability, and progenies quality as well. Similar findings were reported by Saber et al [53] who observed improved hatching and progenies performance when inorganic minerals mixture was replaced with 50% level of organic source in broiler breeder hens.…”
Section: Fertility Hatchability and Chick's Qualitysupporting
confidence: 90%
“…In the current study, the organic Cu improved the fertility, hatchability, and progenies quality as well. Similar findings were reported by Saber et al [53] who observed improved hatching and progenies performance when inorganic minerals mixture was replaced with 50% level of organic source in broiler breeder hens.…”
Section: Fertility Hatchability and Chick's Qualitysupporting
confidence: 90%
“…Mortality rate was significantly reduced in the test group (F4), because, collagen being a potential antioxidant which can inhibit oxidative reaction of free radicals viz., reactive oxygen/nitrogen species which can cause cells death [20]. Seyyed and Hasan [21] reported reduction in mortality by inclusion of omega-3 and omega-6 fatty acids (especially 2% Flax seed oil) in broiler; similarly inclusion of lecithin with choline also had improved the rate of mortality [22]. On an overall comparison, the improvement in performance of broiler chicken muscle growth with comparatively less feed consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, dietary fish oil supplementation could increase calcium absorption in the small intestine and improve bone mineralization and quality in laying hens [ 15 , 96 , 97 ]. In addition, fish oil enriched diet also improves reproductive performance, organs functionality, immunocompetence, skeletal health, and gastrointestinal development in breeder hens [ 14 , 16 , 93 ].…”
Section: Discussionmentioning
confidence: 99%